ACE2 expression is elevated in airway epithelial cells from older and male healthy individuals but reduced in asthma. Issue 5 (17th January 2021) - Wark, Peter A.B.; Pathinayake, Prabuddha S.; Kaiko, Gerard; Nichol, Kristy; Ali, Ayesha; Chen, Ling; Sutanto, Erika N.; Garratt, Luke W.; Sohal, Sukhwinder S.; Lu, Wenying; Eapen, Mathew S.; Oldmeadow, Christopher; et al.
Abstract : ACE2 is the primary receptor for SARS‐CoV‐2. We demonstrate that lower airway expression of ACE2 is increased in older adults and males. Lower ACE2 expression in epithelial cells also occurs in people with asthma and is associated with reduced furin and increased ADAM‐17 expression. This may partly explain the relative sparing of people with asthma from severe COVID‐19. See related Editorial ABSTRACT: Background and objective: COVID‐19 is complicated by acute lung injury, and death in some individuals. It is caused by SARS‐CoV‐2 that requires the ACE2 receptor and serine proteases to enter AEC. We determined what factors are associated with ACE2 expression particularly in patients with asthma and COPD. Methods: We obtained lower AEC from 145 people from two independent cohorts, aged 2–89 years, Newcastle ( n = 115) and Perth ( n = 30), Australia. The Newcastle cohort was enriched with people with asthma ( n = 37) and COPD ( n = 38). Gene expression for ACE2 and other genes potentially associated with SARS‐CoV‐2 cell entry was assessed by qPCR, and protein expression was confirmed with immunohistochemistry on endobronchial biopsies and cultured AEC. Results: Increased gene expression of ACE2 was associated with older age ( P = 0.03) and male sex ( P = 0.03), but not with pack‐years smoked. When we compared gene expression between adults with asthma, COPD and healthy controls, mean ACE2 expression was lower in asthma patients ( P = 0.01). Gene expression of furin, a protease that facilitates viral endocytosis, was also lower in patients with asthma ( P = 0.02), while ADAM‐17, a disintegrin that cleaves ACE2 from the surface, was increased ( P = 0.02). ACE2 protein expression was also reduced in endobronchial biopsies from asthma patients. Conclusion: Increased ACE2 expression occurs in older people and males. Asthma patients have reduced expression. Altered ACE2 expression in the lower airway may be an important factor in virus tropism and may in part explain susceptibility factors and why asthma patients are not over‐represented in those with COVID‐19 complications.